Serum potassium level, variability and in‑hospital mortality in acute myocardial infarction. (22nd March 2022) - Zhang, Xuexue; Wang, Miaoran; Zhu, Zhengchuan; Qu, Hua; Gu, Jiyu; Ni, Tian; Wang, Yi; Wang, Xujie; Zhang, Rui; Li, Qiuyan
Abstract: Objective: Clinical guidelines recommend an optimal serum potassium concentration between 4.0 and 5.0 mmol/L in patients with acute myocardial infarction (AMI), which was based on lower‐quality evidence from more than 20 years ago. Therefore, it is essential to re‐evaluate the range of optimal potassium levels in patients with AMI in intensive care unit (ICU). Methods: This was a retrospective study based on Philips eICU Collaborative Research Database, which covered 9776 patients with AMI between 2014 and 2015. All patients had more than or equal to 2 serum potassium measurements and were categorized by the mean serum potassium level (<3.5, 3.5–4.5, 4.5–5.5, ≥5.5 mmol/L) and potassium variability (1st, 2nd, and ≥3rd standard deviation (SD)). Binary logistic regression was used to determine the association between mean potassium levels, variability and in‑hospital mortality in AMI. Results: Of all 9776 AMI patients in ICU, 8731 (89.3%) patients were included. A total of 69847 potassium measurements were performed in these patients. There was a J‐shaped relationship between mean serum potassium level and in‐hospital mortality. The lowest mortality (mortality rate, 7.2%; 95% CI, 6.57%–7.76%) was observed in patients with mean potassium level between 3.5 and 4.5 mmol/L and a low potassium variability within the 1st SD. Logistic regression showed that the risk of in‑hospital mortality is highest when the mean potassium level ≥5.5 mmol/L (57.6%; 95% Cl, 45.02%–70.24%; multivariable adjusted OR, 14.8; 95% CI, 8.4–26.2) compared to the reference group of 3.5–4.5 mmol/L and potassium variability within the 3rd SD (16.5%; 95% Cl, 15.19%–17.88%; multivariable adjusted OR, 3.3; 95% CI, 2.7–4.1) compared to 1st SD. Several sensitivity analyses confirmed these results. Conclusion: Among AMI patients in ICU, the minimum risk of in‑hospital mortality was observed in those with mean potassium levels between 3.5 and 4.5 mmol/L or a minimal potassium variability compared to those who had higher or lower values.